MEKANISME DAN IMPLEMENTASI PEMUNGUTAN PAJAK KENDARAAN BERMOTOR DI SAMSAT SLEMAN - Susliyanti, Eni Dwi; Somi, Vivilia; Fitriastuti, Lucia Ika; S, Surawan Setya Budi; Iswantoro, Ibnu Yanuar (LP2M STP Mataram, 2024)
This internship activity aims to find out: (1) What is the mechanism for collecting motorized vehicle tax at the Sleman Samsat, (2) the obstacles that occur and the solutions carried out in Motor Vehicle Tax Receipt at the Sleman Samsat. The method of collecting data in solving problems is by interview method, observation method, and by means of the documentation method.The results of this internship show that: (1) The mechanism for collecting motorized vehicle tax in the Sleman Samsat is very good, (2) the obstacles that occur as well as solutions to motorized vehicle tax revenue in the Sleman Samsat, namely, the lack of public awareness in paying motorized vehicle tax properly time, the lack of knowledge of taxpayers regarding the procedure for moving in and out of motorized vehicles in Sleman district and avoidance of progressive tariffs. The solution to overcoming obstacles to motorized vehicle tax collection is to activate tax socialization, hold a motor vehicle tax penalty bleaching/removal program and provide several excellent services that can be used by the community to increase local revenue from motorized vehicle tax while at the same time facilitating the public in carrying out their tax obligations